Peran Perempuan dalam Pengembangan Pariwisata di Kampung Raja Prailiu Kabupaten Sumba Timur - Leni Yaku Danga; Umbu Ho Ara; Yuvensius Ramompas (CV. ALIM'SPUBLISHING, 2026)
This study aims to determine the role of women in tourism development in Raja Prailiu Village, East Sumba Regency, and to identify the obstacles faced by women in tourism activities. This research is motivated by the importance of women's involvement in meeting family economic needs while preserving the weaving culture. This study uses a qualitative descriptive method. Data were obtained through observation, interviews, and documentation. Research informants consisted of six women who are active in tourism activities in Raja Prailiu Village. Data sources used include primary data from interviews and secondary data from books, journals, articles, and related documents. Data analysis techniques used the Miles and Huberman model which includes data reduction, data presentation, as well as drawing conclusions and verification. The results of the study show that women have an important role in tourism development, namely as weavers, craft product sellers, tour guides, and actors in preserving culture and cleanliness of the tourist environment. However, women also face various obstacles, such as increasing the number of tourists, high prices of raw materials, limited time due to dual roles, lack of English language skills, and low tourist awareness of environmental cleanliness. This research contributes to showing the importance of the role of women in tourism development and becomes a consideration for the government and the community in supporting tourism development in Raja Prailiu Village.